Risk factors associated with increased coronary calcium score and carotid intima media thickness in asymptomatic type 2 diabetic patients - Mitevska, I; Kostova, N; Vavlukis, M; Zdravkovska,M; Lazarova, E; Bosevski, M (My University, 2019)
Aim.The aim of the study was to evaluate the association between standard risk factors, glycated hemoglobin (HgA1C), high –sensitive C reactive protein (hs-CRP) and increased coronary calcium score (CCS) and carotid intima media thickness(c-IMT) as markers of vascular atherosclerosis. Metods: We have evaluated 68 diabetes type 2 patents with high cardiovascular risk without known coronary artery disease(CAD).Multislice computer tomography was performed for assessment of CCS.Total and regional CCS was amalyzed using Agatston units(AU).Carotid ultrasound was performed to evaluate c-IMT.Univariate and multivariate stepwise forward logistic regression analysis was performed including the following parameters:diabetes duration, age,body mass index, total cholesterol, LDL, HDL, non-HDL, triglycerides, sex, smoking, hypertension, dyslipidemia, HgA1C, estimated glomerular filtration rate (eGFR: mL/min/1.73 m2) and hs-CRP values. Results: CCS<UAU was found in 46 patients(67.6%), CCS >100AU was present in 21 patients(30.8%).Average CCS was 127+/-35. After univariate analysis, multivariate stepwise forward analysis found smoking(OR 4.61,p<0.001), HgA1C% (OR 3.68,p<0.001),and hs-CRP>2 mg/l (OR 3.61 p<0.001) as independent predictors for CAC>0AU.The value od CCS increased with age, smoking and dyslipidemia, all p<0.01.Increased c-IMT was found in 51 patients (75%).Independent predictors for increased c-IMT >0.8 mm were smoking,(OR 5.71, p<0.001),dyslipidemia (OR4.43, p<0.001), hypertension (OR 5.70,p<0.001) and eGFR (OR 3.98, p<0.01).CCS>100AU was significantly associated with increased incidence od c-IMT (p<0.001).Patients with increased c_IMT and CCS>100AU had an average 2 risk factors.Conclusion: Increased CCs and c-IMT were significantly associated with increased hs_CRP>2 mg/l, the estimated glomerular filtration rate, hypertension, dyslipidemia and smoking. Elevated CCS increase risk of extra coronary atherosclerosis.The study confirms the cumulative effect of risk factors and inflammation on vascular wall.
Keywords: risk factors; coronary calcium score